Antiarrhythmic mechanisms of beta blocker therapy. (August 2019) - Grandi, Eleonora; Ripplinger, Crystal M.
Highlights: β-Blockers are effective antiarrhythmics in many cardiac diseases. β-Adrenergic effects on cardiac function are complex, and involve changes occurring over multiple time- and spatial-scales. Future studies are needed to improve personalization of β-blockade therapy for varying arrhythmia types and patient groups. Key aspects to consider are receptor-specific drug action, compartmentalized signaling, and sex differences. Graphical abstract: Abstract: Sympathetic activity plays an important role in modulation of cardiac rhythm. Indeed, while exerting positive tropic effects in response to physiologic and pathologic stressors, β-adrenergic stimulation influences cardiac electrophysiology and can lead to disturbances of the heart rhythm and potentially lethal arrhythmias, particularly in pathological settings. For this reason, β-blockers are widely utilized clinically as antiarrhythmics. In this review, the molecular mechanisms of β-adrenergic action in the heart, the cellular and tissue level cardiac responses to β-adrenergic stimulation, and the clinical use of β-blockers as antiarrhythmic agents are reviewed. We emphasize the complex interaction between cardiomyocyte signaling, contraction, and electrophysiology occurring over multiple time- and spatial-scales during pathophysiological responses to β-adrenergic stimulation. An integrated understanding of this complex system is essential for optimizing therapies aimed at preventing arrhythmias.